Supplementary stimulation, short-term memory and anxiety in young people - Montgomery Urday, William (2002)
Is the purpose to explore some relations beetwen anxiety and cognition through a factorial design 2 X 2 with even groups of seventeen subjects each one. The experiment consist in to manage to subjects with autorefering anxiety and no that, a type of stimulation evoked negative emotional responses (angry, fear, sadness and sick), after to memorize during for two minutes a words list with positive, negative and neutral meaning. Its supposing the subjects with plus or minor anxiety level tends to memory more negative emotional words. This is confirmed only in the plane of simultaneous function anxiety-supplementary stimulation. Was conc1uded that high activation state anxiety maked prone the subjects pay any attention and remember threatening stimulus.